Metabolomics analysis in adults with high bone mass identifies a relationship between bone resorption and circulating citrate which replicates in the general population. (20th November 2019) - Hartley, April; Paternoster, Lavinia; Evans, David M.; Fraser, William D.; Tang, Jonathan; Lawlor, Debbie A.; Tobias, Jon H.; Gregson, Celia L.
Abstract: Objective: Bone turnover, which regulates bone mass, may exert metabolic consequences, particularly on markers of glucose metabolism and adiposity. To better understand these relationships, we examined cross‐sectional associations between bone turnover markers (BTMs) and metabolic traits in a population with high bone mass (HBM, BMD Z‐score ≥+3.2). Design: β‐C‐terminal telopeptide of type‐I collagen (β‐CTX), procollagen type‐1 amino‐terminal propeptide (P1NP) and osteocalcin were assessed by electrochemiluminescence immunoassays. Metabolic traits, including lipids and glycolysis‐related metabolites, were measured using nuclear magnetic resonance spectroscopy. Associations of BTMs with metabolic traits were assessed using generalized estimating equation linear regression, accounting for within‐family correlation, adjusting for potential confounders (age, sex, height, weight, menopause, bisphosphonate and oral glucocorticoid use). Results: A total of 198 adults with HBM had complete data, mean [SD] age 61.6 [13.7] years; 77% were female. Of 23 summary metabolic traits, citrate was positively related to all BTMs: adjusted ββ‐CTX  = 0.050 (95% CI 0.024, 0.076), P  = 1.71 × 10 −4, βosteocalcin  = 6.54 × 10 −4 (1.87 × 10 −4, 0.001), P  = .006 and βP1NP  = 2.40 × 10 −4 (6.49 × 10 −5, 4.14 × 10 −4 ), P  = .007 (β = increase in citrate (mmol/L) per 1 µg/L BTM increase). Inverse relationships of β‐CTX (β = −0.276 [−0.434, −0.118], P  = 6.03 × 10 −4 ) and osteocalcin (−0.004 [−0.007, −0.001], P  = .020) with triglycerides were also identified. We explored the generalizability of these associations in 3664 perimenopausal women (age 47.9 [4.4] years) from a UK family cohort. We confirmed a positive, albeit lower magnitude, association between β‐CTX and citrate (adjusted βwomen  = 0.020 [0.013, 0.026], P  = 1.95 × 10 −9 ) and an inverse association of similar magnitude between β‐CTX and triglycerides (β = −0.354 [−0.471, −0.237], P  = 3.03 × 10 −9 ). Conclusions: Bone resorption is positively related to circulating citrate and inversely related to triglycerides. Further studies are justified to determine whether plasma citrate or triglyceride concentrations are altered by factors known to modulate bone resorption, such as bisphosphonates.